PERANCANGAN SISTEM INFORMASI OPTIK PADA SALSA FORTUNA BERBASIS WEB - Taufik Fathurrahman; Tantri Wahyuni (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Optik Salsa Fortuna is a business engaged in the sale of optics that provides a variety of glasses, frames, contact lenses, eyeglass cleaning fluid and other optical accessories, which is located on Jl.Raya K H Abdul Halim No.396, Majalengka Wetan.The problems faced by the Salsa Fortuna Optical Shop include problems in processing goods data that are still not computerized, there is no proof of transactions such as proof of sale. Another problem that exists at the Salsa Fortuna Optic Shop is that they often experience difficulties in checking stock, there is no sales report prepared and their profits are only using a recap of notes for reports.Based on the problems above, we need an information system that can help process goods data, sales reports and profits by combining components that have not been computerized into one system so that later they can be used in business processes to make them more effective and faster, in making the system using the waterfall method which is very suitable in solving this problem. The purpose of this research is to find out the system that is running at Optik Salsa Fortuna, then evaluate and find problems that hinder business processes at Optik Salsa Fortuna, to make it easy for shops to record transactions which of course will generate sales reports and profit reports. precise and accurate, and to implement a sales information system at Optics Salsa Fortuna, so that it can solve existing problems